Management as a profession: a typology based assessment. Issue 9 (15th October 2019) - Segon, Michael John; Booth, Chris; Pearce, Jeremy
Abstract : Purpose: The purpose of this paper is to establish a typology of a profession and to then assess the circumstances under which management could be classified as a profession against such a typology. Design/methodology/approach: The current paper is conceptual. The research approach consists of formulating a typology of a profession based on the literature research methodology. The resulting typology is applied to assess management as a profession. Findings: Although there have been efforts in recent literature and media commentary to position management as a profession, no thorough conceptually based analysis to rigorously analyze nor test this claim against the dominant arguments in the literature has been undertaken. The typology presents comprehensive research and analysis across disciplines to identify the circumstances under which management could be considered a profession. Research limitations/implications: The paper offers a complete typology upon which to classify a profession. It provides highly supported arguments to discern elements of a profession. The key limitation lies in capturing and organizing extensive concepts and views across diverse literature disciplines to refine a holistic perspective (i.e. accountancy, business management, ethics, psychology and sociology). Practical implications: This conceptual typology enables the design of a highly operable assessment system. It considers requisite standards for professions. It also informs potential professional bodies of the obligations to which they and their members must adhere to achieve and retain the status of a profession. Originality/value: A comprehensive typology indicating the interdependent requirements and obligations required by a profession has not been espoused in either popular business journals or academic journals across the discipline areas now covered by this research investigation. The contribution provides a comprehensive academic argument to answer the question: can management be considered a profession?